A Colonial‐Scientific Interface: The Construction, Viewing, and Circulation of Faces via a 1906 German Racial Atlas. Issue 2 (6th May 2020) - Mak, Geertje
ABSTRACT: Atlases of anthropometric portraits—a scientific genre that emerged during the last quarter of the nineteenth century in the context of classical physical anthropology—invite readers to compare different races from all over the world. Concentrating on Bernard Hagen's Atlas of Heads and Faces of Asian and Melanesian People (1906), this article describes the apparatus that enabled such a way of viewing. A microanalysis of Hagen's facial atlas reveals the circumstances under which the portraits were produced, the reading strategies the atlas stimulates, as well as the reification of data through their circulation. It shows how precisely a facial atlas could function as an imperceptible interface between harsh colonial practices and German public support for colonizing "missions, " between individual subjectivity and racialized category, and between everyday colonial recognition and scientific analysis of "races." Obscuring the apparatus facilitating such a vision naturalizes the position of a viewer surveying, analyzing, and comparing people of different geographic backgrounds as races. [ colonial history, photography, face, racial science, Dutch East Indies ] RESUMEN: Los atlas de retratos antropométricos —un género científico que emergió durante el último cuarto del siglo XIX en el contexto de la antropología física clásica— invitan a los lectores a comparar diferentes razas de todas partes del mundo. Al concentrarse en el Atlas de cabezas y rostros de personas asiáticas y melanesias (1906) de Bernard Hagen, este artículo describe el aparato que permitió tal manera de ver. Un microanálisis del atlas facial de Hagen revela las circunstancias bajo las cuales los retratos fueron producidos, las estrategias de lectura que el atlas estimula, así como la reificación de datos a través de su circulación. Muestra cómo precisamente un atlas facial puede funcionar como una interface imperceptible entre las prácticas coloniales duras y el apoyo público alemán por las "misiones" colonizadoras, entre la subjetividad individual y la categoría racializada, y entre el reconocimiento colonial cotidiano y el análisis científico de "razas." Al oscurecer el aparato que facilita tal visión naturaliza la posición de un espectador que inspecciona, analiza, y compara personas de antecedentes geográficos diferentes como razas. [ historia colonial, fotografía, rostro, ciencia racial, Indias Orientales Holandesas ]